Penanggulangan Pelanggaran Hak Cipta Pembajakan CD/VCD - Hasniah Hasniah (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2020)
This study aims to identify and analyze the phenomenon of copyright infringement of compact disk or video compact disk (CD/VCD) piracy and to identify and analyze the prevention of the copyright infringement in Biak Numfor. The approach used in this research was empirical juridical research. Data collection techniques used were observation and interviews. The results show that the emergence of CD/VCD piracy cannot be set apart from the socio-economic conditions that exist in the Biak’s community. This condition is a strong foundation for hijackers to make low-cost hijacked products. The development of piracy cannot be separated from the role of the community, where the public as consumers not only feel innocent by buying hijacked products, but often feel benefited from the very cheap price of CD/VCD cassettes. Efforts to overcome copyright infringement in Biak are preventive and repressive efforts.